Use of period analysis to timely assess 5-year relative survival for breast cancer patients from Taizhou, Eastern China - Li, Runhua; Zheng, Yabing; Huang, Jiajia; Lei, Huijun; Xu, Mingzhi; Wang, Liangyou; Zhang, Luyao; Cheng, Yongran; Jiang, Xiyi; Tang, Huijuan; Shi, Zheng; Chen, Gang; et al. (Frontiers in Oncology, 2022)
Objectives While timely assessment of long-term survival for patients with breast cancer is essential for evaluation on early detection and screening programs, those data are extremely scant in China. We aimed to derive most up-to-date survival estimates and to predict future survival using the cancer registry data from Taizhou city, Eastern China. Methods Patients diagnosed with breast cancer during 2004-2018 from four cancer registries with high-quality data from Taizhou, Eastern China were included. Period analysis was used to calculate 5-year relative survival (RS) for the overall population and according to the stratification factors sex, age at diagnosis and geographic region. We further predict the upcoming 5-year RS during 2019-2023, using continuous data from three 5-year periods (2004-2008, 2009-2013 and 2014-2018) and a model-based period approach. Results Overall 6159 patients diagnosed with breast cancer during 2004-2018 were enrolled. The 5-year RS for breast cancer in 2014-2018 reached 88.8%, while women were higher compared to men (90.5% versus 83.7%) and urban areas were higher compared to rural areas (91.9% versus 86.7%). Additionally, we found a clear gradient by age at diagnosis, ranging from 94.8% for age<45 years to 83.3% for age>74 years. Projected overall 5-year RS for the upcoming 2019-2023 could reach 91.5% (84.8% for men and 93.5% for women). Conclusions We provided, for first time in China, using period analysis, most up-to-date 5-year RS (88.8%) for patients with breast cancer from Taizhou, Eastern China. We also demonstrate the 5-year RS has improved greatly over last 15 years, which has important implications for timely evaluation of early detection and screening programs.